Autonomy And Autogenesis: Practitioner Research And The Self-Made Literacy Tutor - Ralf St. Clair; Kathy Maclachlan (Adult Education Research Conference, 2009)
Examines the conduct of a practitioner-led action research program in Scottish literacy, and challenges the extent to which PLAR can be adopted as a professional development strategy. Expresses caution about the potential for PLAR to reinforce individualized and managerial approaches to the field as promoted by new public management.